A high efficiency boost converter topology with least component count - Swargiary, Rikhit; Deva Sarma, Kaushik Chandra (Institute of Advanced Engineering and Science, 2024)
This paper presents a design and analysis of novel DC-DC boost converter with a least component count. The proposed converter produces high DC gain voltage in comparison to some recently presented high voltage DC-DC converter. Here one switch, one inductor, two capacitors and one diode are used to achieved a high voltage gain without compromising efficiency of converter. The converter’s performance is evaluated using theatrical, simulation and experimental methods, with results indicating a four times of input voltage and a fast-transient response at various duty cycles is achieved. Due to its low component count the proposed converter is compact and hence it offers an effective solution for various power applications.